Nutrição mineral e escleromorfismo foliar de grupos funcionais e comunidades vegetais savânicas - Souza, Marcelo Claro de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Savannas (located in Australia, Brazil and South Africa) hold the second largest biodiversity on the planet. These savannas have developed their vegetation structure on acidic and nutrient-poor soils, under a well-defined dry and rainy seasons. Among the limiting ecological filters, fire, soil fertility, water availability and herbivory are considered the most important ones. Other filters, which may be considered subfilters of the soil fertility are acidity and aluminum (Al) availability in the soil. Aluminum is considered a toxic element for most plant species, however savanna plants are insensitive to Al, and some species are Al-accumulators. We studied leaf nutritional status, Al accumulation and leaf scleromorphism of savanna species at three levels: regional, national and intercontinental. For national and intercontinental analysis we evaluated variations in the annual 9 rainfall, soil fertility and soil acidity. At the regional level, we compared leaf scleromorphism, nutritional status, Al accumulation, leaf phenology and the concentration of secondary metabolites in young and mature leaves of Al-accumulator and non-accumulator species in a cerrado remnant in Itirapina-SP. At the national level we compared the nutritional status, Al accumulation and leaf scleromorphism variations between two cerrado sensu stricto (s. str.) fragments:, one in the core region (Brasília - DF) and another on the southeastern periphery of the cerrado (Itirapina - SP). On a global scale, we studied the dissimilarities on the nutritional status, Al accumulation and leaf scleromorphism between the Australian, Brazilian and South African savannas. At the regional level, we observed two distinct strategies of leaf development between Al-accumulator and non-accumulator species. At the national level, we concluded that the peripheral cerrado community was less scleromorphic than the community in the core. These variations were explained by the higher soil...

As savanas (localizadas na Austrália, África do Sul e Brasil) abrigam a segunda maior biodiversidade do planeta. Tais savanas se desenvolveram sobre solos ácidos, pobres em nutrientes e com estações secas e chuvosas bem definidas. Dentre os filtros ecológicos limitantes à manutenção das savanas, fogo, fertilidade do solo, disponibilidade hídrica e herbivoria são considerados os mais importantes. Outros filtros muito importantes, mas considerados subfiltros da fertilidade do solo são: acidez do solo e disponibilidade de alumínio (Al). O Al é considerado um elemento tóxico para a maior parte das plantas, entretanto as espécies savânicas são consideradas insensíveis ao Al, sendo algumas espécies inclusive acumuladoras. Desta forma, foi estudado o perfil nutricional, acúmulo de Al e escleromorfismo foliar de espécies savânicas em três níveis: regional, nacional e intercontinental. Para os níveis nacional e intercontinental acrescentamos as variações de pluviosidade anual, fertilidade e acidez do solo. Em nível regional comparamos as variações no grau de escleromorfismo, concentração de nutrientes foliares, acúmulo de Al, fenologia e produção de metabólitos secundários em folhas jovens e maduras de espécies acumuladoras e não acumuladoras de Al em um fragmento de cerrado em Itirapina – SP. Em nível nacional comparamos as variações das concentrações de nutrientes foliares, acúmulo de Al e escleromorfismo foliar entre dois fragmentos de cerrado sensu stricto (s. str.): um na região central (Brasília – DF) e o outro na borda sudeste do cerrado (Itirapina – SP). Em escala global, estudamos as variações nutricionais, acúmulo de Al e escleromorfismo foliar entre as savanas Australiana, Brasileira e Sul Africana. Em escala regional observamos dois padrões distintos de desenvolvimento foliar entre os dois grupos de espécies. Em escala nacional, observamos menor ecleromorfismo e maior acúmulo...
Keywords: Plant physiology; Fisiologia vegetal; Plantas - Nutrição; Comunidades vegetais; Savanas; Ecologia das savanas; Cerrados; Aluminio; Ecossistemas; Ecofisiologia vegetal